Shoja Azari and Shahram Karimi: The Cold Earth Sleeps Below - Azari, Shoja; Karimi, Shahram (NY; Leila Heller Gallery, 2016)
Shoja Azari is an Iranian-born visual artist and filmmaker based in New York City. He is known for his films and multimedia installations. Shahram Karimi is an Iranian self-taught painter and video artist. Exhibition from Feb-Mar 2016 @ Leila Heller Gallery, NYC.
English
Keywords: N4390-5098 Exhibitions; Iran